Analysis Of The Use Of Standard And Non-Standard Language In Food Content On Youtube - Fauziah; Erlinda Simbolon; Yola Febriani Br Purba; Norven Togatorop; Salmin Wanimbo (Outline Journal of Education, 2026)
This study analyzes the use of standard and non-standard language in culinary content on YouTube, focusing on their roles and functions in digital communication. The rapid development of digital technology has transformed communication patterns, with platforms like YouTube becoming primary spaces for interaction, especially in popular genres such as culinary content where creators often blend language styles. The hypothesis suggests that non-standard language is more dominant as it effectively builds audience engagement, while standard language ensures clarity and professionalism. A descriptive qualitative method with observation and note-taking was applied by analyzing a culinary video from Ria SW’s channel, specifically the episode titled “Medan Food Diaries: My Top 6 Picks”. Data was collected through meticulous transcription and analyzed using content analysis to classify language variations and their pragmatic functions. The findings reveal that non-standard language predominates in creating a casual and persuasive atmosphere, while standard language serves to deliver clear information. Standard language is strategically employed to convey factual details about food, such as ingredients or objective taste descriptions, to maintain credibility. In contrast, non-standard forms, including popular slang like “mantul” and other expressive phrases, are instrumental in fostering closeness and authenticity, making the content more relatable. The study concludes that both language varieties complement each other; standard language maintains the informative quality, while non-standard language enhances the entertainment value and viewer connection. These findings provide valuable implications for sociolinguistic studies and Indonesian language learning through digital media, demonstrating how language flexibly adapts to modern communication needs.